Workshop Writing in Composing Paragraph to Improve Students' Writing Skills at SMA Negeri 1 Sampolawa'S Eighth Grade - Hasrida Ardin; Hikmawati Hikmawati (Hasanuddin University, 2024)
The purpose of this study was to determine whether or not using collaborative writing to compose paragraphs improves students' writing abilities at SMA Negeri 1 Sampolawa's VIII grade students. It also sought to determine whether or not using collaborative writing sparks students' interest in writing. An experiment using a quassi design was used in this study. Cluster random sampling was utilized as the sample-taking technique, with two classes out of three being taken. 25 students from the XI IPA-2 class were separated into an experimental group by the researcher. and the XI IPA-1 class, which served as the control group, had 25 students. As a result, 50 students made up the research sample. The test and questionnaire served as the study instrument. The research tool was categorized using multiple methods. Pretest, posttest, and questionnaire were those.The results of this study demonstrated that, following treatment with the collaborative writing approach, students' English writing proficiency increased. Based on the experimental group's pretest mean score of 65.97 and posttest mean score of 77.23. The research's hyphotesis resulted in notable effects. Based on the average student perception score of 3,87—a very high level—it is determined.